(untitled) (The Journal of Plant Protection Sciences, 2022)
Botanicals or plant extracts from Cathranthus roseus, Coleus aromaticus , Manilkara zapota and Azadirachta in dica was studied by poisoned food technique, seed germination and under green house experiments for control of Colletotrichum capsici, fungal pathogen responsible for anthracnose disease in bell peppers (Capsicum frutescence L.). The results showed that all the selected plants have potential to inhibit the radial mycelial growth of C. capsici in-vitro. The plant extract from C. aromaticus at 50% concentration showed 42% radial mycelial growth inhibition in poisoned food technique, whereas 15% increased seed germination and 26% reduced disease incidence is re coded when compared to untreated control. In pot experiments, there is an increase in height and weight of the plants by 22% and 44% respectively in seeds treated with C. aromaticus when compared to chemical fungicide Bavistin and also 13% reduction in disease incidence is observed when compared to untreated control. From the results it is evident that C. aromaticus were effective in not only controlling the disease but also increase the height and weight of the plants and hence are highly recommended for plant disease control.